Digitalisation, institutions and governance, and growth: Mechanisms and evidence - Vincent Labhard; Jonne Lehtimäki (European Central Bank (ECB), 2022)
Digitalisation may be viewed as a sequence of supply and technology shocks affecting the economy through productivity and output, employment and labour markets, competition and market structure. This paper focuses on the effects of digitalisation on economic growth, and how those effects may be impacted by institutions and governance. It discusses a number of theoretical mechanisms and empirical evidence for different sets of European and other countries. The results suggest that better institutions and governance tend to be associated with greater growth-enhancing effects from digital technologies.
Keywords: E22; O33; O43; O52; O57; 330; technology; adoption; estimates; pooled mean group estimation (PMGE); panel